PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR EKONOMI SISWA KELAS X SMA NEGERI 3 SELONG - Jailani, Huzain; Musyarrofah, Ratna Laila (Universitas Hamzanwadi, 2019)
This study studies to learn whether applying a problem solving learning model can improve learning and learning outcomes of class X students in SMA Negeri 3 selong 2019/2020 academic year, this study uses classroom action research (Classroom Action Research) with research subjects in class X IPS 2 SMA 3 selong. While the data collection techniques used are observation and learning achievement tests.The results showed that the application of the problem solving learning model could increase the activities and learning outcomes of students of class X IPS 2 in SMA Negeri 3 Selong in the 2019/2020 study year. This was discussed by increasing the grade average grade and learning here during the second cycle learning ie the average grade of 60.22 increased to 80.87 and classical learning completeness with a value of 43.48% increased to 86.96%, As for the score of student learning activities also showed an increase with a score of 2.4 to 2.8 with the category of quite active